Methods of Calculating and Reducing Sampling Error - Nasima Sawlat,; Hayatullah Masomi, (Journal of Mathematics and Statistics Studies, 2025)
Sampling error is a significant factor in research, denoting the variance between sample statistics and actual population values. This study examines techniques for quantifying and mitigating sampling error to improve the reliability and accuracy of research findings. Essential methods for determining sampling error, such as the standard error of the mean, confidence intervals, proportional error estimates, and bootstrapping, are examined comprehensively. Strategies to mitigate sampling error, including augmenting sample size, using stratified sampling, utilizing systematic sampling, implementing weighted adjustments, and enhancing sampling frames, are examined. The results underscore the significance of rigorous sampling techniques in reducing error, guaranteeing representativeness, and improving the validity of outcomes. The research emphasizes the significance of sophisticated statistical methodologies and pilot studies in mitigating constraints in sampling methods. This study offers pragmatic insights and methodological directives for academics, policymakers, and practitioners in several fields. It also delineates avenues for further investigation, including the use of sophisticated computational techniques and context-specific sampling methodologies, to further reduce sample error and enhance study quality.